PENGARUH PENYUNTIKAN EKSTRAK KELENJAR HIPOFISA DARI LIMBAH KEPALA IKAN PATIN SIAM Pangasionodon hypophtalmus (Sauvage, 1878) TERHADAP PENINGKATAN PERFORMA PEMIJAHAN IKAN KOMET Carassius auratus (Linnaeus, 1758) - Elisdiana, Yeni; Astuti, Reni; Utomo, Deny Sapto C; Hudaidah, Siti (JARI : Jurnal Akuakultur Rawa Indonesia, 2024)
Goldfish (Carassius auratus) is one of the freshwater ornamental fish whose fry production has not been able to full fill market demand. Artificial spawning is one way to increase the production of goldfish fry. The purpose of this study was to evaluate the effect of injecting striped catfish pituitary gland extract (Pangasionodon hypophtalmus) on the spawning performance of goldfish. The research design used a completely randomized design (CRD) with 4 treatments and 3 replications, the treatment was of injections of pituitary gland extract with different doses, namely, A (pituitary gland 0 mg/kg fish), B (pituitary gland 250 mg/kg fish), C (pituitary gland 500 mg/kg fish), and D (pituitary gland 750 mg/kg fish). The results of the study showed the injection of the striped catfish pituitary gland (Pangasionodon hypophtalmus) increases the level of gonadal maturity (TKG), while the parameter such as relative fecundity, egg diameter, and fertilization rate had no significant effect (P>0.05). Key words: Striped Catfish Head Waste, Goldfish, Pituitary Gland, Spawning Performance